PERANCANGAN DAN PEMBUATAN TETARING BALE GONG DENGAN BAHAN KUAT DAN SENI - Gunantara, N.; Sasmita, G.M.A.; Dwijendra, N.K.A.; Mataram, I.M.; Harsana, I.K.G. (Buletin Udayana Mengabdi; Vol 21 No 2 (2022): Buletin Udayana MengabdiDO - 10.24843/BUM.2022.v21.i02.p10, 2022)
Bale Gong is a very important building in the temple. This is because every ceremony at the temple is accompanied by a gamelan gong. In every piodalan ceremony at Sindetan Temple always make a tent for the Bale Gong. Tents that are installed are usually made of materials that are easily damaged, namely bamboo, coconut leaves, and tie rope. In making these tents, it takes a lot of people who have expertise and cost of making the tent is quite expensive. After completing the ceremony, the tent is dismantled where the materials cannot be reused at the next piodalan ceremony. This is because these materials will break down quickly. The solution to this problem and at the same time is the goal of this service is in the form of innovation in making tents from strong and durable materials. The materials that will be used are iron and cloth. This iron is used instead of bamboo and cloth is used instead of slepan and tie rope. The final result of this service is has designed and made tent that are strong, aesthetic, comfortable, and easy to assemble and disassemble. The tents that have been made are installed in Bale Gong and then handed over to the residents of Sindetan Temple.   Keywords: Bale Gong, Sindetan Temple, tent, design, strong, aesthetic.